2015
DOI: 10.1139/apnm-2014-0243
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-induced hyperhydration decreases urine output and improves fluid balance compared with glycerol- and water-induced hyperhydration

Abstract: Before 2010, which is the year the World Anti-Doping Agency banned its use, glycerol was commonly used by athletes for hyperhydration purposes. Through its effect on osmoreceptors, we believe that sodium could prove a viable alternative to glycerol as a hyperhydrating agent. Therefore, this study compared the effects of sodium-induced hyperhydration (SIH), glycerol-induced hyperhydration (GIH) and water-induced hyperhydration (WIH) on fluid balance responses. Using a randomized, double-blind and counterbalance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 108 publications
(151 reference statements)
0
11
2
Order By: Relevance
“…A simple and legal way to enhance plasma volume is to induce hyperhydration prior to exercise using glycerol. Indeed, glycerol-induced hyperhydration (GIH) has been shown to increase total body water by ~ 800 mL and plasma volume by ~ 8% [ 5 , 6 , 7 ] 2 h following the ingestion of 26 mL of water/kg body mass (BM) with 1.2 g of glycerol/kg BM.…”
Section: Introductionmentioning
confidence: 99%
“…A simple and legal way to enhance plasma volume is to induce hyperhydration prior to exercise using glycerol. Indeed, glycerol-induced hyperhydration (GIH) has been shown to increase total body water by ~ 800 mL and plasma volume by ~ 8% [ 5 , 6 , 7 ] 2 h following the ingestion of 26 mL of water/kg body mass (BM) with 1.2 g of glycerol/kg BM.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, research involving these strategies are scarce. The interest of pre-exercise hydration recommendations have shown that the consumption of beverages with high amounts of sodium and different types of carbohydrates can reduce fluid loss and improve fluid balance during exercise [1,8]. Previous research involving pre-exercise consumption of chicken soup [9] and non-alcoholic beer [10] have shown improved fluid balance during exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a greater proportion of the beverages ingested were CES in DF. This may have resulted in a greater sodium intake in DF and, therefore, better fluid retention and fluid balance compared to other positions [ 33 ]. One possible explanation is that MD and FW performed more runs and may not tolerate the ingestion of large volumes of fluids during training, consequently resulting in lower total fluid intake [ 34 ].…”
Section: Discussionmentioning
confidence: 99%